Kontribusi Ekonomi Islam dalam Membentuk Kesejahteraan Ekonomi dan Sosial Global - Maulana, Anas Wahid; Maulana, Isnan Sayid (Darul Yasin Al Sys, 2024)
This study aims to investigate the contribution of Islamic economics in shaping economic and social well-being globally. Through literature analysis and empirical studies, the study identifies the underlying principles of Islamic economics, including justice, equality, and balance, and evaluates their impact on various aspects of economic and social life in different countries. The research methods used include document analysis and case studies of the implementation of Islamic economic principles in various contexts. The results highlight that Islamic economics has played a significant role in increasing financial inclusion, promoting sustainable economic growth, and alleviating poverty and inequality. The implications of this research provide valuable insights for policymakers, economic practitioners, and the general public in efforts to promote global economic and social well-being.